Pengembangan Kurikulum Berbasis Sains untuk Peningkatan Literasi Teknologi - Rudiprayitno, Aji; Afifa, Dinda Nur; Susanti, Adin Ardia; Mahardika, I Ketut; Mahmudi, Kendid (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2024)
Science is a way to study how nature works and unravel mysteries systematically. Science plays an important role in our daily lives, because science makes it easier for us to know the world around us and helps ease our work. Science and technology are two things that are related, with science creating new technology and technology creating new knowledge. The pace of development of science and technology is accelerating, but the human capacity to adjust to technological advances is limited or slow. The rapid development of the times produces increasingly high technology and experts in physics, biology, chemistry and others compete to create increasingly sophisticated, quality and environmentally friendly technology. This also affects the field of education. With the rapid development of technology, educators should utilize the technology as a learning tool to support learning activities. There have been many applications of the integration between technology and education such as classroom, zoom and even kahoot! The better quality of education will build a foundation for creating more qualified human resources and can be useful for advancing world civilization.